The FBI a history - Jeffreys-Jones, Rhodri (Yale University Press, 2007)
This fast-paced history of the FBI presents the first balanced and complete portrait of the vast, powerful, and sometimes bitterly criticized American institution. Rhodri Jeffreys-Jones, a well-known expert on U.S. intelligence agencies, tells the bureaus story in the context of American history. Along the way he challenges conventional understandings of that story and assesses the FBI's strengths and weaknesses as an institution." "Common wisdom traces the origin of the bureau to 1908, but Jeffreys-Jones locates its true beginnings in the 1870s, when Congress acted in response to the Ku Klux Klan campaign of terror against black American voters. The character and significance of the FBI derive from this original mission, the author contends, and he traces the evolution of the mission into the twenty-first century.